The shaping of social capital in buyer-supplier relationships and entrepreneurial activities in a dual perspective - Sin, Yat Hong/Y.H. (2010)
This research examines the shaping of buyer-supplier relationship by social capital in a dual perspective. It has provided evidences of different factors, include human capital, industry, and firm strategy, affected the development of social capital in different pace between buyer and supplier. It also examined the shaping of entrepreneur activities by social capital. It has provided evidences of the relational and structural dimensions of social capital has great influence in entrepreneur activities. It also further strengthen understanding of the importance of human capital in maximizing the benefits of social capital.